THE REFINEMET OF FRAMEWORK STRUCTURES OF NATURAL MORDENITE AND CLINOPTILOLITE CRYSTALS USING RIETVELD METHOD - Supandi Suminta (Institut Teknologi Bandung, 2005)
Framework structures of clinoptilolite and mordenite phases in natural zeolit from Bayah have been succesfully analysed using Rietveld Method. The diffraction intensity data were collected using X-Ray Difractometer (XRD) at P3IB-BATAN. The refinement of the clinoptilolite and mordenite phases have been carried out and the results show that there are poly cation K-Mg clinoptilolite phase, with space group symmetry of C2/m No.12, monoclinic crystal system and poly cation Ca-Na mordenite phase, with space group symmetry of Cmcm No.63, orthorombic crystal system. Chemical formulas of clinoptilolite and mordenite phases are (K5,17 Mg0,16) (Al6Si30O72). 24H2O and [(Na 5,63 Ca 1,13) (Al8Si40O96). 22H2O per unit cell respectively. Fitting quality (goodness-of-fit) gave a value of Rwp = 10,34%.